Improved chemical stability of silver by selective distribution of silver particles on reduced graphene oxide nanosheets1. Issue 61 (4th July 2015) - Tang, Xiu-Zhi; Chen, Xuelong; Wu, Gang; Hu, Xiao; Yang, Jinglei
<x xml:space="preserve">Abstract</x> The chemical stability of silver particles on RGO was greatly improved by choosing a suitable sequence of "deoxygenation" and "deposition".